2018
DOI: 10.1111/eth.12758
|View full text |Cite
|
Sign up to set email alerts
|

Soft songs in male ortolan buntings are used in an aggressive context but are not an aggressive signal

Abstract: Many bird species produce low‐amplitude acoustic signals that have been poorly studied in comparison with loud, broadcast songs used for mate attraction and repelling rivals. In some birds, these soft signals were found to be emitted in an antagonistic context and were the most reliable predictor of a subsequent physical attack. The function of this signal is poorly understood, and several hypotheses have been proposed to explain the mechanisms and possible functions of such low‐amplitude signals. The subject … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…Like Budka et al (2019), we had the subjective impression that males sometimes changed the amplitude of their rain calls, although we did not measure vocal amplitudes. Low-amplitude songs and calls are often used by songbirds in an aggressive context during territorial interactions (e.g., Hof and Hazlett 2010;Searcy et al 2014;Akçay et al 2015;Jakubowska and Osiejuk 2018). If rain calls are a substitute for song and are also used to maintain territory occupancy, their low-amplitude versions may be used in a similar way as soft songs, in order to confirm if the intruder is still present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like Budka et al (2019), we had the subjective impression that males sometimes changed the amplitude of their rain calls, although we did not measure vocal amplitudes. Low-amplitude songs and calls are often used by songbirds in an aggressive context during territorial interactions (e.g., Hof and Hazlett 2010;Searcy et al 2014;Akçay et al 2015;Jakubowska and Osiejuk 2018). If rain calls are a substitute for song and are also used to maintain territory occupancy, their low-amplitude versions may be used in a similar way as soft songs, in order to confirm if the intruder is still present.…”
Section: Discussionmentioning
confidence: 99%
“…Various aspects of birdsong have been found to be associated with different outcomes in territorial conflicts (Vehrencamp 2000; Communicated by H. Brumm Beecher 2009). In addition to repertoire size (Balsby et al 2017;Byers 2017), song performance parameters such as frequency matching (Morton and Young 1986;Horn et al 1992), soft song (Hof and Hazlett 2010;Jakubowska and Osiejuk 2018), vocal performance (Moseley et al 2013;Phillips and Derryberry 2017), or song-type matching (Krebs et al 1981;King and McGregor 2016) can play a role during aggressive interactions by birds.…”
Section: Introductionmentioning
confidence: 99%
“…However, twenty years of research on a continuous and abundant population from Western Poland has revealed no age‐related changes in repertoire size, contents or overall song diversity (e.g. Skierczyński & Osiejuk, ; Osiejuk, Bielecka & Skierczyński, ; Jakubowska & Osiejuk, ; own unpubl. data).…”
Section: Discussionmentioning
confidence: 99%
“…1). In an earlier experimental study we tested whether the soft songs of the Ortolan Bunting are a signal of increased aggressiveness (Jakubowska and Osiejuk 2018). We found that soft song in this species does not meet the context, prediction and response criteria of aggressive signal specified by Searcy and Beecher (2009).…”
Section: Introductionmentioning
confidence: 93%
“…Males respond stronger to loud songs than to soft ones and did not treat soft song as a predictor of signal escalation. However, depending on the type of experiment, soft songs appeared in 40-60% of simulated intrusions, but the occurrence of such songs was usually low in comparison to broadcast songs (Jakubowska and Osiejuk 2018;own unpublished material). The research mentioned above may suggest that soft song can be a tool to decrease the active range of signal, but the reason for this change was not tested explicitly.…”
Section: Introductionmentioning
confidence: 98%